INVESTIGATION OF THE FREQUENCY OF DAMAGE TO HEATING NETWORKS: Array - Grankina, V.; Maliavina, O.; Milanko, V. (Municipal economy of cities. Series: «Economy science», 2020)
This article is devoted to improving the efficiency of planning the consumption of material and technical and labor resources and their appropriate planning for heating and non-heating periods, by months of the year based on the calculation of the estimated number of damage to heating pipes, based on the obtained dependences of failure rate. This task is modern and relevant especially in conditions of limited funding of engineering systems. The object of study - the district heating system. The subject of research - pipelines of thermal networks. The purpose of the work is to determine the distribution of damage to the heating network pipelines by months. The research method is statistical modeling of damages of heating network pipelines by months of the year for different terms of their operation. Currently, the reliable operation of district heating systems and their heating networks is one of the main factors in the livelihood of settlements. The reliability of heating network pipelines is determined by the reliability indicators obtained on the basis of data on the damage of heating pipelines. Studying the distribution of the number of damages of heating network pipelines by months depending on the service life of heating pipelines is necessary for effective planning of material, technical and labor resources. In order to increase the efficiency of planning of material and technical and labor resources, it is advisable to calculate the number of damages for the heating and unheated periods, by months of the year, by decades. The calculated dependences of the distribution of damage to the pipelines of heating networks for the heating and non-heating periods on a monthly basis, decadally, should take into account the service life of the pipelines. The results of the above research will save material, technical, labor and energy resources.